1999
DOI: 10.1002/(sici)1521-3935(19990701)200:7<1639::aid-macp1639>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the free-radical copolymerization of butyl acrylate with methyl methacrylate

Abstract: SUMMARY: Free-radical copolymerization of butyl acrylate with methyl methacrylate was carried out at 50 8C in a 3 mol/L benzonitrile solution. Differences between the apparent reactivity ratios determined in this work with those previously reported in bulk, toluene and benzene indicate noticeable solvent effects. This fact can be explained through different models, but independent of the chemistry of the system, to obtain the same copolymer composition in bulk or in solution, the monomer feed that should be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The influence of the polarity of the reaction medium has been put forward since the first papers on the effect of solvents on copolymerization parameters were published 1, 4, 5, 22. Thus, two different and opposite trends, as a function of the solvent polarity, also have been observed for MMA/BA copolymerizations performed in benzene or benzonitrile 29. Furthermore, the effect of solvent polarity on the local monomer concentration has been noted when 2‐hydroxyethyl methacrylate is copolymerized with S in solvents with a low dipole moment (toluene) or with a high dipole moment ( N , N ′‐dimethylformamide) 30.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the polarity of the reaction medium has been put forward since the first papers on the effect of solvents on copolymerization parameters were published 1, 4, 5, 22. Thus, two different and opposite trends, as a function of the solvent polarity, also have been observed for MMA/BA copolymerizations performed in benzene or benzonitrile 29. Furthermore, the effect of solvent polarity on the local monomer concentration has been noted when 2‐hydroxyethyl methacrylate is copolymerized with S in solvents with a low dipole moment (toluene) or with a high dipole moment ( N , N ′‐dimethylformamide) 30.…”
Section: Resultsmentioning
confidence: 99%
“… 23 By applying heat to the silane agent, the solvent of the agent sufficiently evaporates, increasing the chemical responsiveness of the silane coupling agent. 24 For dental applications, several previous studies have already used the heat activation technique and evaluated its effectiveness on the bonding of fiber posts to resin composites. For example, Monticelli et al 21 concluded that drying at a high temperature (38℃) may facilitate the evaporation of solvents in silane agents, eventually improving the bonding strength of the dual-cure composite resin to the fiber post (the study used D.T.…”
Section: Discussionmentioning
confidence: 99%
“…But, in this study heat treatment after silanization of the post was not effective in enhancing bond strength. Silane coupling is a technique-sensitive step, given that incomplete evaporation of the solvent may compromise chemical reactions between silane and the glass or quartz fibers of the post 19. Heat treatment after application of the silane coupling agent is thought to promote complete evaporation of the solvent.…”
Section: Discussionmentioning
confidence: 99%